Assessment of Heavy Metal Contamination and Health Risks in Road Deposited Sediments: A Study in Owerri, Nigeria - Odochi, Ubechu Bridget; Enimakpokpo , Joan; Akaolisa , Casmir Chukwuemeka Zanders; Agbasi, Okechukwu; Nwachukwu, Helen (Ecological Questions, 2024)
The study aims to conduct an ecological risk assessment and build a pollution model for assessing trace metal concentrations in road dust in Owerri, Nigeria. Key roadways in the urban area were chosen based on traffic volume, population density, and human activity. Data was collected at 500-meter intervals throughout each route, and silt samples were collected by systematic sweeping of a 1 square metre area covering road pavements and curbs. The examination found metallic pollutants such as chromium (Cr), manganese (Mn), iron (Fe), cobalt (Co), nickel (Ni), copper (Cu), zinc (Zn), and lead (Pb) inside the RDS. Nickel (Ni), copper (Cu), cadmium (Cd), and lead (Pb) levels were substantially higher than their respective background values. Carbon monoxide levels along Port Harcourt Road, specifically 670 mg/l, are much higher than the background norm, indicating a considerable influence of human activity. Estimated enrichment values for the metallic elements ranged from insignificant (Mn) to extremely high (Co, Ni, Cu, Zn, Pb). Based on geoaccumulation index data, it can be concluded that the RDS has significant levels of contamination in terms of Ni and Pb, implying a considerable buildup of certain heavy metals, most likely due to anthropogenic acts. The study identified two major sources of heavy metal contamination: natural sources originating in the Earth's crust and transportation-related activities such as air deposition, corrosion, and vehicle degradation.